Enhancing natural product extraction and mass transfer using selective microwave heating - Lee, Chai Siah; Binner, Eleanor; Winkworth-Smith, Charles; John, Rebecca; Gomes, R.L.; Robinson, John (Elsevier, 2016)
This study uses a combination of empirical observations and an analysis of mass transfer behaviour to yield new insights into the mechanism of microwave assisted extraction. Enhancements in extraction rate and yield were observed experimentally compared with conventional extraction at temperatures in excess of 50°C, however at lower temperatures there was no observable difference between the two processes. A step-change in extract yield between microwave and conventional processes was shown to be caused by selective heating. A temperature gradient of the order of 1oC is sufficient to reduce the water chemical potential within the cell structure, which changes the osmotic potential such that internal cell pressures can increase to the point where disruption occurs. This paper demonstrates the need to operate microwave extraction processes at a temperature that enables selective heating, and a newly-proposed mass transfer phenomenon that could have wider positive implications for extraction and leaching processes.